(untitled) (Communications in Computational Physics, 2010)
We are interested in the modeling of wave propagation in an infinite bilayered acoustic/poroelastic media. We consider the biphasic Biot's model in the poroelastic layer. The first part was devoted to the calculation of analytical solution in two dimensions, thanks to Cagniard de Hoop method. In the first part (Diaz and Ezziani, Commun. Comput. Phys., Vol. 7, pp. 171-194) solution to the two-dimensional problem is considered. In this second part we consider the 3D case.